Psychological Well-Being Reviewed by The Work Complacency of The Employees of PT. Abs - Sri Hartini; Angelyn Tania; Chaterine Simwira; M. Hafizh Raihan; Mukhaira El Akmal; Sabrini Mentari Rezeki (Eduvest - Journal of Universal Studies, 2024)
The study is held in PT. Andalan Bintang Sampali working environment. The objective is to obtain the bond among the job satisfaction with psychological well-being of PT. Andalan Bintang Sampali’s employees. Population and sample on this research is: 102 (a hundred and two) employees of PT. Andalan Bintang Sampali. The method of Purposive Sampling is being used as the technique to collect samples. The technique of gathering data is by disseminate the questions-form to those samples. Analysis technique that is being carried out in this study/research is the Correlational Pearson Product Moment technique.The results of the research found a correlation between work satisfaction and psychological well-being with the correlation coefficient F = 0.947 as well as p = 0.000 (p<0.01). The assumption test composed of normality test, linearity trial, correlation check, descriptive test, as well as effective contribution test. The data was outlined with SPSS 27 for Windows by using Correlation Pearson Product Moment technique. Research shows that the effective contribution shows that 94.7 percent occured within job satisfaction and psychologial well-being, while the rest 5.3 percent lie on other factors that weren’t being researched.